2010
DOI: 10.1111/j.1364-3703.2009.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitogen‐activated protein (MAP) kinase signalling components and the Ste12 transcription factor in germination and pathogenicity of Botrytis cinerea

Abstract: SUMMARYIn all fungi studied so far, mitogen-activated protein (MAP) kinase cascades serve as central signalling complexes that are involved in vari~us aspects of growth, stress response and infection, In this work, putative components of the yeast Fus3/Kss1-type MAP kinase cascade and the putative downstream transcription factor Ste12 were analysed in the grey mould fungus Botrytis cinerea. Deletion mutants of the MAP triple kinase Ste11, the MAP kinase kinase Ste7 and the MAP kinase adaptor protein Ste50 all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
139
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 38 publications
3
139
0
Order By: Relevance
“…In addition, germ tubes continue to elongate on hydrophobic surfaces and never differentiate appressoria, indicating that they are defective in signaling leading to appressorium formation (Fig. 2B) (27,30). By comparing gene expression in wild-type and bmp1 mutant germlings, we aimed to identify genes that are involved in the appressorium differentiation process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, germ tubes continue to elongate on hydrophobic surfaces and never differentiate appressoria, indicating that they are defective in signaling leading to appressorium formation (Fig. 2B) (27,30). By comparing gene expression in wild-type and bmp1 mutant germlings, we aimed to identify genes that are involved in the appressorium differentiation process.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their role in germination, the cAMP and the BMP1 MAPK signaling pathways are required for appressorium differentiation, penetration, and host colonization, similar to the situation in other plant-pathogenic fungi (31,32). The MAPK cascade ste11, ste7, bmp1, and ste50 mutants did not form appressoria on hard surfaces, they failed to penetrate into host tissue, and they were nonpathogenic (27,30). Other signaling elements found to be involved in germination are the small GTPase Cdc42 and phospholipase C (Plc1) (33).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…26 The contribution of alveolar epithelial cells in fungicidal defense was demonstrated by in vitro studies as well as in murine infections, thereby affecting the immunotolerant disposal of inhaled A. fumigatus conidia. Matthias Hahn from the University of Kaiserslautern, Germany, next gave an overview about the spread and fitness of multi-resistant strains of the necrotrophic plant pathogen Botrytis cinerea 27 and described a role of a sensor protein, Sho1, related to BMP1 MAPK signaling 28,29 in pH modulation. Interestingly, sho1 mutants phenocopy the lack of velvet complex components such as Vel1 or Lae1; 30 however, transcriptional profiling studies in planta revealed similarities but also significant differences, leaving the connection between Sho1 and the velvet complex an open issue.…”
Section: Feeding From the Host -Nutrition And Metabolism (Session 1)mentioning
confidence: 99%